Synthesis, EGFR Inhibition and Anti-cancer Activity of New 3,6-dimethyl-1-phenyl-4-(substituted-methoxy)pyrazolo[3,4-d] pyrimidine Derivatives - B. Bakr, Rania; B. M. Mehany, Ahmed; R. A. Abdellatif, Khaled (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Several pyrazolo[3,4-d]pyrimidine derivatives have been reported as anti-cancer agents via acting as EGFR inhibitors, mammalian target of rapamycin (mTOR) inhibitors, Src or dual Src/Abl inhibitors, glycogen synthase kinase-3b (GSK-3b) inhibitors or cyclin dependent kinase (CDK) inhibitors. Objective: A new series of hybrid pyrazolo[3,4-d]pyrimidine scaffold with a heteroaryl moiety as pyrazole, oxadiazole, triazole or phthalimide moiety (14a-f, 16, 17, 19, 20) was synthesized and biologically evaluated for the cytotoxicity against human liver cancer cell line (HEPG-2), human breast cancer cell line (MCF-7) and human colon cancer cell line (HCT-116). Results and Method: While the pyrazolo hybrid compounds (14a-f) showed good activity against HEPG-2, MCF- 7 and HCT-116 cell lines (IC50 = 3.65 – 39.98, 1.45 – 54.19 and 2.00 – 50.6 µM respectively) in comparison with doxorubicin (IC50 = 5.66, 2.60 and 8.48 µM respectively), the triazolo derivatives (17, 19) showed considerable potency (IC50 = 22.20 – 54.61, 14.98 – 88.78, and 10.79 – 53.40 µM respectively), the oxadiazolo hybrid compound (16, IC50 = 149.91, 115.89 and 110.07 µM respectively) and phthalimido hybrid compound (20, IC50 = 96.02, 131.19 and 120.36 µM respectively) showed low potency. The pyrazolo derivative (14d, IC50 = 3.65, 1.45 and 2.00 µM) was the most potent among all compounds against HEPG-2, MCF-7 and HCT-116 cell lines respectively. Also, the hybrid pyrazolo[3,4-d]pyrimidine derivatives were evaluated for their inhibitory activity to epidermal growth factor receptor tyrosine kinase (EGFR-TK) and they showed a good inhibitory activity (IC50 = 8.27 – 19.03 µM). With the exception of the pyrazolo derivative (14c, IC50 = 18.82 µM), the inhibitory activity against EGFR-TK was consistent with the in vitro cytotoxic activity against HEPG-2, MCF-7 and HCT-116 cell lines. Conclusion: The newly synthesized compounds showed good activity against HEPG-2, MCF-7 and HCT-116 cell lines in comparison with the reference drug doxorubicin.
Keywords: Anti-cancer activity